Frequency of Left Ventricular Mechanical Dyssynchrony in Chronic Heart Failure - Zahoor Ahmad Khan, Javaidullah Khan, Hameedullah, Salman Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of left ventricular mechanical dyssynchrony in chronic heart failure patients. Material and Methods: After approval from the Hospital ethical committee, the study was conducted in the department of cardiology Hayatabad medical complex Peshawar from 1st September 2021 to 28th February 2022. In this descriptive cross-sectional study, 155 patients in total were examined while 27% of heart failure patients had mechanical dyssynchrony, a 95% confidence interval, and a 7% margin of error were maintained according to WHO sample size computations. Results: This study’s participants had an average age of 60, with a standard deviation of ±1.26 years. 62% of the patients were male, compared to 38% of females. 35% of patients had a Broad QRS complex, whereas 65% of patients had a Narrow QRS complex. Mechanical dyssynchrony was identified in 32% of chronic heart failure patients. Conclusion: Patients in chronic heart failure with QRS > 150ms and having mechanical dyssynchrony are benefited with Cardiac Ressynchronisation Therapy (CRT) implantation which reduces morbidity and mortality, while those with a narrow QRS (<150ms) are generally non – responders. Keywords: Mechanical dyssynchrony, chronic heart failure, left ventricular ejection fraction